CHANGES IN COAGULATION PROFILE IN PATIENTS UNDERGOING LAPAROSCOPIC CHOLECYSTECTOMY WITH CARBON DIOXIDE PNEUMOPERITONEUM - Dr Kshetra Mohan Tudu; Dr Samarendra Satpathy; Dr Rashmi Ranjan Palai; Dr Pabitra Hembram; Dr Rajat Kumar Dash; Dr Snigdha Bharati Samal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Laparoscopic cholecystectomy is a widely performed surgical procedure. The use of carbon dioxide pneumoperitoneum during this surgery may impact the coagulation profile of patients. This study aims to investigate the effects of carbon dioxide pneumoperitoneum on coagulation parameters and assess the potential risk of thrombosis.Methodology: A clinical observational study was conducted on 113 patients undergoing laparoscopic cholecystectomy with carbon dioxide pneumoperitoneum. Prothrombin time and D-dimer levels were measured before and after surgery. Data were analyzed using the paired t-test.Results: The study revealed a post-operative decrease in prothrombin time and an increase in D-dimer levels. Specifically, the mean post-operative prothrombin time was 0.159 seconds shorter than the pre-operative value, while D-dimer levels were three times higher than pre-operative levels. Both results were statistically significant.Conclusion: Laparoscopic cholecystectomy with carbon dioxide pneumoperitoneum induces a hypercoagulable state. Therefore, rigorous measures should be implemented to provide prophylaxis against deep vein thrombosis to prevent serious complications.